The effect of security concern and perceived ease of use on repurchase intention: the role of e-trust and e-satisfaction as mediators - Rahmiati, Rahmiati; Adini, Hasti; Hasan, Alizar; Pujani, Vera; Games, Donard (Jurnal Kajian Manajemen Bisnis, 2023)
This study aims to analyze (1) security concern and perceived ease of use on repurchase intention: the role of e-trust and e-satisfaction as mediators (2) The effect of security, perceived ease of use, repurchase intention of the role of trust and satisfaction as a mediator. The populace utilized in this study is all clients of E-business applications and the example involved is clients of E-trade applications in Bukittinggi City somewhere twice involving E-business for web-based shopping. The quantity of tests utilized in this review was 200 respondents. Information was gathered through an internet-based survey (google form) and information about the executives utilizing PLS (Partial Least Square) programming. The results of this study indicate that. (1) Security concern has a significant effect on repurchase intention (2) perceived ease of use has a significant effect on repurchase intention (3) security concern has a significant effect on repurchase intention (4) e-satisfaction has a significant effect on repurchase intention (5) security concern has a significant effect on repurchase intention through trust (6) perceived ease of use has a significant effect on repurchase intention through e-satisfaction (7). Perceived ease of use has a significant effect on repurchase intention through e-satisfaction (7). Perceived ease of use has a significant effect on repurchase intention through security concerns (8). e-satisfaction a siginifikan effect on repurchase intention through trust. The results of this study indicate that it is positively and significantly influenced by security, convenience, and repurchase intention mediated by e-trust and e-satisfaction.